The effect of ownership structure on financial distress with audit committee as moderating variable - Widhiadnyana, I Kadek; Wirama, Dewa Gede (International research journal of management, IT and social sciences, 2020)
The purpose of this study is to obtain empirical evidence about the effects of managerial ownership and institutional ownership on financial distress and examine the role of the audit committee in moderating the effect of managerial ownership and institutional ownership on financial distress. The sampling technique used is the nonprobability sampling method with a purposive sampling technique. The data used in this study are secondary data obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. Data are analyzed using ordinal logistic regression. The results of the analysis show that managerial ownership has no effect on financial distress, institutional ownership has a negative effect on financial distress, and the audit committee does not moderate the relationship between either managerial ownership or institutional ownership on financial distress.